Suicidal thoughts (ideation) among elite athletics (track and field) athletes: associations with sports participation, psychological resourcefulness and having been a victim of sexual and/or physical abuse - Timpka, T.; Spreco, A.; Dahlstrom, O.; Jacobsson, J.; Kowalski, J.; Bargoria, V.; Mountjoy, M.; Svedin, C. G. (British Journal of Sports Medicine, 2021)
Objective To examine associations between suicidal ideation and sexual and physical abuse among active and recently retired elite athletics (track and field) athletes.Methods The study population consisted of all athletes (n=402) selected for a Swedish Athletics team between 2011 and 2017. Data on suicidal ideation, suicidal events (estimated through the 1 year non- sports injury prevalence), lifetime abuse experiences, sociodemographics, sense of coherence and coping strategies were collected using a cross- sectional survey. The data were analysed using binary logistic regression with suicidal ideation and non- sports injury as outcomes.results 192 athletes (47.8%) returned data. The prevalence of suicidal ideation was 15.6% (men 17.4%; women 14.2%) and the non- sports injury prevalence was 8.0% (men 11.6%; women 5.7%). Among women, suicidal ideation was associated with having been sexually abused (OR 5.94, 95% CI 1.42 to 24.90; p=0.015) and lower sense of coherence (OR 0.90, 95% CI 0.85 to 0.96; p=0.001) (Nagelkerke R2=0.33). Among men, suicidal ideation was only associated with use of behavioural disengagement for coping (OR 1.51, 95% CI 1.18 to 1.95; p=0.001) (R2=0.25). Among women, non- sports injury prevalence was associated with having been sexually abused (OR 8.61, 95% CI 1.34 to 55.1; p=0.023) and participating in an endurance event (OR 7.37, 95% CI 1.11 to 48.9; p=0.039 (R2=0.23), while among men, having immigrant parents (OR 5.67, 95% CI 1.31 to 24.5; p=0.020) (R2=0.11) was associated with injury outside sports.Conclusions About one out of six international athletics athletes reported having experienced suicidal ideation. World Athletics and National Olympic Committees need to include suicide prevention in their athlete protection programmes.